'I will do it but religion is a very personal thing': teacher education applicants' attitudes towards teaching religion in Ireland. Issue 2 (15th March 2018) - Heinz, Manuela; Davison, Kevin; Keane, Elaine
Abstract: There has been extensive research internationally describing teachers' homogenous socio-demographic backgrounds and critiquing the associated equity and diversity issues, most especially with regard to ethnicity and gender, and to a lesser extent, social class and disability. Yet, teachers' religious affiliations and/or convictions have rarely been explored. Since 96% of state primary schools in Ireland are denominational, considering religious diversity in teaching is both critically important and a complex undertaking. This paper examines primary initial teacher education (ITE) applicants' religiosity, and views of teaching religion, in Ireland. Our data suggest low levels of religious practice and religiosity among ITE applicants, many of whom would prefer to teach religion using a non-confessional approach. The paper raises critical questions regarding the experiences, constitutional rights and professional practice of increasingly secular and/or non-practicing Catholic teacher cohorts in a predominantly Catholic primary education system that has survived the trend towards progressive 'unchurching' of Europe.